PEMBANGUNAN APLIKASI ArIPA BERBASIS ANDROID (Studi kasus: SMP Muhammadiyah Cianjur) - Buhori Muslim; Asep Saputra; Emil Herdiana; Widianjani (JURNAL ILMIAH BETRIK, 2023)
Teaching and learning activities, are activities aimed at making students become intelligent, independent, careful, in carrying themselves in their lives, to become so, the important role of 2 (two) learning elements is needed, namely teacher professionalism and learning media (means). The focus of this research is on learning media, at Muhammadiyah Cianjur Middle School based on learning observations only using textbooks, or adding additional student worksheets, so that the acceptance of the material is not optimal resulting in not optimal achievement. This research is based on observations and information from the subject curriculum. What is of concern is science subjects, so based on this information a science learning application or multimedia was built using augmented reality technology so that the application is called ArIPA, because there is a lot of science discussion, ArIPA only discusses Astronomy, using the MDLC development method. So that an application is produced that is able to support teaching and learning science subjects, sub-chapter Astronomy, the application has been tested and all tools and application menus are in accordance with the learning objectives